PHOTOPHORESIS OF FLAVONOIDS IN COMPREHENSIVE TREATMENT OF PATIENTS WITH GENERALIZED PERIODONTITIS - I.Z. Chubiy; M.M. Rozhko (Український стоматологічний альманах)
The aim of the study was the new approach to methods of treatment of patients with generalized periodontitis by adding laser radiation and quercetin to the complex therapy. Scientists suggest that the use of physical therapy is necessary with almost all forms and stages of development of generalized periodontitis (GP) to diagnose illness symptomatic treatment, adjuvant therapy, prevention of disease in persons living under ecologically unfavorable conditions. Important features of physiotherapeutic treatment are stimulation of non-specific tissue reactivity and protective properties of the organism. After their usage activity of the elements of connective tissue and phagocytic activity of leukocytes are increased, tissue regeneration processes are accelerated, the application of laser therapy with quercetin promote recovery of antioxidant system, normalization of cell membrane potential and improving oxygen uptake by tissues become evident.